Analisis Peran Petugas Imigrasi di Bandara Internasional dalam Keseimbangan Fungsi Administratif dan Keamanan Negara - Doniartha Jalu Abdi; Imma Yedida Ardi; Agung Sulistyo Purnomo (Lembaga Pengembangan Kinerja Dosen, 2025)
This article discusses the dual role of immigration officers at international airports, encompassing both administrative functions and national security. As an agency responsible for overseeing the movement of foreign nationals and granting residence permits, immigration officers play a critical role in supporting public administration while also safeguarding national security. This study adopts a literature review approach with a qualitative descriptive method to examine various aspects related to the duties and challenges faced by immigration officers in performing these dual functions. The analysis reveals that immigration officers face role conflicts caused by high workloads, insufficient training, and suboptimal use of technology. On the security front, officers act as the first line of defense in detecting and preventing threats that could destabilize the nation. The discussion also includes a comparison of immigration practices in countries such as Australia, the United States, and Japan, which show that integrating administrative and security functions can enhance border control effectiveness. The article concludes with recommendations to strengthen the capacity of immigration officers, both in terms of training and technology, as well as improving inter-agency coordination to enhance the performance of Indonesia's immigration system.